Determinants of culture success in an airway epithelium sampling program of young children with cystic fibrosis - Garratt, L.; Sutanto, E.; Foo, C.; Ling, K.; Looi, K.; Kicic-Starcevich, E.; Iosifidis, T.; Martinovich, K.; Lannigan, F.; Stick, S.; Kicic, Anthony (Taylor & Francis, 2014)
Copyright © 2014 Informa Healthcare USA, Inc. Aim of the study: The bronchial brushing technique presents an opportunity to establish a gold standard in vitro model of Cystic Fibrosis (CF) airway disease. However, unique obstacles exist when establishing CF airway epithelial cells (pAEC < inf > CF < /inf > ). We aimed to identify determinants of culture success through retrospective analysis of a program of routinely brushing children with CF. Materials and methods: Anaesthetised children (CF and non-CF) had airway samples taken which were immediately processed for cell culture. Airway data for the CF cohort was obtained from clinical records and the AREST CF database. Results: Of 260 brushings processed for culture, 114 (43.8%) pAEC < inf > CF < /inf > successfully cultured to passage one (P1) and 63 (24.2% of total) progressed to passage two (P2). However, > 80% of non-CF specimens (pAEC < inf > non-CF < /inf > ) cultured to P2 from similar cell numbers. Within the CF cohort, specimens successfully cultured to P2 had a higher initial cell count and lower proportion of severe CF mutation phenotype than those that did not proliferate beyond initial seeding. Elevated airway IL-8 concentration was also negatively associated with culture establishment. Contamination by opportunistic pathogens was observed in 81 (31.2% of total) cultures and brushings from children with lower respiratory tract infections were more likely to co-culture contaminating flora. Conclusions: Lower passage rates of pAEC < inf > CF < /inf > cultures uniquely contrasts with pAEC < inf > non-CF < /inf > despite similar cell numbers. An equivalent establishment rate of CF nasal epithelium reported elsewhere, significant associations to CFTR mutation phenotype, elevated airway IL-8 and opportunistic pathogens all suggest this is likely related to the CF disease milieu.